The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10689-006-9109-5
|View full text |Cite
|
Sign up to set email alerts
|

An association between the 4G polymorphism in the PAI-1 promoter and the development of aggressive fibromatosis (desmoid tumor) in familial adenomatous polyposis patients

Abstract: Aggressive fibromatosis is a mesenchymal neoplasm associated with mutations resulting in beta-catenin mediated transcriptional activation. Plasminogen activator inhibitor-1 (PAI-1) is expressed at a high level in aggressive fibromatosis, and using transgenic mice, we found that PAI-1 plays an important role in aggressive fibromatosis tumor formation. Familial adenomatous polyposis is associated with Adenomatous Polyposis Coli gene mutations resulting in beta-catenin mediated transcriptional activation, yet onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(45 reference statements)
1
1
0
Order By: Relevance
“…Our results revealed PAI‐I 4G/4G genotype significantly increase the risk of endometrial carcinoma and the elevated risk reached statistic significance in the whole study group and the subgroups of those patients over 50 years old, endometrioid type and low stage (stages I–II) endometrial cancer. The finding are in accordance with those of previous studies that showed PAI‐1‐675 4G/4G genotype is associated with increased risk for oral cancer 11, 13, aggressive fibromatosis 14, and breast cancer 15.…”
Section: Discussionsupporting
confidence: 93%
“…Our results revealed PAI‐I 4G/4G genotype significantly increase the risk of endometrial carcinoma and the elevated risk reached statistic significance in the whole study group and the subgroups of those patients over 50 years old, endometrioid type and low stage (stages I–II) endometrial cancer. The finding are in accordance with those of previous studies that showed PAI‐1‐675 4G/4G genotype is associated with increased risk for oral cancer 11, 13, aggressive fibromatosis 14, and breast cancer 15.…”
Section: Discussionsupporting
confidence: 93%
“…4,5 Less frequently reported aberrations include reduced expression of the Retinoblastoma (RB) tumor suppressor gene, 6 upregulation of Wilms' tumor gene 1 (WT1), 7 and polymorphism in the plasminogen activator inhibitor 1 (PAI-1) promoter. 8 Epidermal growth factor (EGF) and transforming growth factor alpha (TGFa) are essential participants in the process of wound healing and their common receptor (EGFR) is typically upregulated in uteroplacental tissues during childbirth. [9][10][11][12][13] Overexpression of EGFR also correlates with tumor aggressiveness in a variety of cancer types.…”
mentioning
confidence: 99%